2006
DOI: 10.1111/j.1551-2916.2006.00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Homogeneity of Particle Coordination on Solid‐State Sintering of Transparent Alumina

Abstract: A quantitative assessment of the homogeneity of particle coordination in green bodies is achieved by addressing pore structures. Avoiding a coarser tail of the pore size distribution is important but insufficient for optimum sintering. Instead, the steepest slope of the main body of the distribution is responsible for a maximum density at lowest temperature, and further progress is enabled by minimizing interparticle spacing (the average pore size). Ranking different technologies with different associated pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(124 citation statements)
references
References 12 publications
(24 reference statements)
9
109
3
3
Order By: Relevance
“…Alumina ceramics have a long clinical history and are proven to have excellent biocompatibility and biological safety [6,16]. To our knowledge, no study to date has reported the in vivo biocompatibility or bone tissue compatibility of CNT/alumina composites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alumina ceramics have a long clinical history and are proven to have excellent biocompatibility and biological safety [6,16]. To our knowledge, no study to date has reported the in vivo biocompatibility or bone tissue compatibility of CNT/alumina composites.…”
Section: Discussionmentioning
confidence: 99%
“…Then, two-step polymerase chain reaction (PCR) was performed using a real-time PCR detection system (DNA Engine Opticon system, MJ Japan, Tokyo, Japan ) with primers (Takara Bio, Shiga, Japan) specific to Runx 2, osteocalcin, or 16 glyceraldehyde-3-phosphate dehydrogenase. The fold/change ratios between the test specimens were calculated.…”
Section: Quantification Of Calciummentioning
confidence: 99%
See 1 more Smart Citation
“…Over recent years, attempts have been made to replace sapphire by transparent polycrystalline alumina (PCA) [1][2][3][4][5][6] for both economic and ecological reasons.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Cases where these interactions are of importance are, among others, the fabrication of high quality green bodies, for highly transparent ceramics, [2,3] or colloidal preparation routes for advanced powders, for example, by hetero coagulation. [4] Ceramic thin or thick films for porous films for ink-jet paper coatings [5] and piezoelectric screen printing applications [6] also depend greatly on the rheological properties and quality of dispersion.…”
Section: Introductionmentioning
confidence: 99%